Customer loyalty in e-retailing: an exploratory study. (12th September 2005) - La, Khanh V.; Walker, Rhett; Kam, Booi
This study explores the nature and dimensionality of customer loyalty within an online retailing context. Results show that many types of consumer behaviours that are typically attributed to customer loyalty in the traditional, offline context can also be found in the web-based environment. The analysis also indicates that the attitudinal dimension of e-loyalty itself is multi-dimensional and can be considered as a function of customers' present and future predispositions towards a retailer. The research highlights the complex nature of e-loyalty that is evident through the way in which its different components relate differently to one another. Two levels of e-loyalty are identified, both of which are multi-dimensional and are important to web-based retailers in different ways.